2009
DOI: 10.1177/0023830909336584
|View full text |Cite
|
Sign up to set email alerts
|

Phonetic Specificity in Early Lexical Acquisition: New Evidence from Consonants in Coda Positions

Abstract: Use of precise consonantal information while learning new words has been established for onset consonants in previous studies, which showed that infants as young as 16 to 20 months of age can simultaneously learn two new words that differ only by a syllable-initial consonant (Havy & Nazzi, 2009; Nazzi, 2005; Nazzi & New, 2007; Werker, Fennell, Corcoran, & Stager, 2002). However, there is no systematic evidence to show whether specific phonetic information in other positions within the syllable can be used whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
52
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 48 publications
9
52
4
Order By: Relevance
“…Thus, the phonotactic pattern involved the co-occurrence of classes of consonants and their typical word positions. The divergence between our findings and those of Nazzi and Bertoncini (2009) may have occurred because young word learners are more sensitive to overall phoneme frequency differences than to phonotactic patterns based on word position, phoneme combinations, or non-adjacent relationships. Learning of phoneme co-occurrence probabilities that is sufficiently robust to affect label learning may require more language experience than learning patterns of individual phoneme frequencies at given word positions, because co-occurrence patterns require storing and detecting even more highly detailed information.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Thus, the phonotactic pattern involved the co-occurrence of classes of consonants and their typical word positions. The divergence between our findings and those of Nazzi and Bertoncini (2009) may have occurred because young word learners are more sensitive to overall phoneme frequency differences than to phonotactic patterns based on word position, phoneme combinations, or non-adjacent relationships. Learning of phoneme co-occurrence probabilities that is sufficiently robust to affect label learning may require more language experience than learning patterns of individual phoneme frequencies at given word positions, because co-occurrence patterns require storing and detecting even more highly detailed information.…”
Section: Discussioncontrasting
confidence: 97%
“…We selected this manipulation because overall phoneme frequency is a potentially strong manipulation of phonotactics that is well suited to young learners (Coady & Aslin, 2004). Nazzi and Bertoncini (2009) used a different definition of phonotactic patterns and found that 20-month-olds did not differentiate between labels that varied in phonotactics. Nazzi and Bertoncini tested French infants’ learning of monosyllabic labels that differed in the positions of labial and coronal consonants; in French words (and many other languages), labials (e.g., /b/ or /p/) frequently precede coronals (e.g., /d/ or /t/) (MacNeilage, Davis, Kinney, & Matyear, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Word learning tasks with pairs of words differing by one phoneme reveal that French-learning toddlers are sensitive to consonant but not to vowel contrasts until the age of 30 months (Havy & Nazzi, 2009;Nazzi, 2005;Nazzi & Bertoncini, 2009;Nazzi, Floccia, Moquet, & Butler, 2009;Nazzi & New, 2007). Moreover, even older French-learning children and French adults show a consonant bias in word learning tasks (Havy, Bertoncini & Nazzi, 2011;Havy et al, in press).…”
mentioning
confidence: 99%
“…No significant differences were found in children's ability to perceive segmental contrasts in word-initial compared to word-final position, adding to the research that finds no effect of word position in children's perception and production (Nazzi & Bertoncini 2009;Zamuner 2009). The lack of a position effect might reflect participants' stage of development in the study, where the average age of participants was 2;5.…”
Section: Discussionmentioning
confidence: 71%